The specificity of Several Kinds Lipases on n-3 Polyunsaturated Fatty Acids - Jenny Elisabeth; T Yuliani; P M Tambunan; J M Purba (Jurnal Teknologi dan Industri Pangan, 2001)
Several lipases from microbial and plant, i.e Rhizomucor miehei, Pseudomonas sp., Candida antartica, rice bran, and Carica papaya latex (CPL) were examined for synthesis of omega-3 (n-3) PUFA-rich glyceride by hydrolysis and acidolysis reaction. Tuna oil was used in hydrolysis reaction, whereas tuna and palm oils were used as source of triglyceride (TAG) molecules and n-3 PUFA concentrate from tuna oil as source of EPA and DHA in acidolysis reaction.For hydrolysis reaction, the rice bran and CPL lipases showed the lowest hydrolytic activity of the tuna oil, whereas the R. miehei lipase showed the highest hydrolytic activity but was unable to hydrolyze EPA and DHA. On the contrary, the C. antartica and Pseudomonas sp. lipases acted stronger on hydrolysis of DHA ester bond than EPA.For acidolysis reaction, all the lipases showed ability to incorporate n-3 PUFA into tuna and palm oils. C. antartica lipase had the maximum DHA incorporation into tuna and palm oils, rice bran lipase had relatively similar ability with R. miehei lipase, and the CPL lipase had the lowest ability. This study proved that rice bran and CPL lipases also had transesterification activity and showed the feasibility of the rice bran lipase to be a biocatalyst for n-3 PUFA-rich glyceride production. Increasing the substrate ratio, of n-3 PUFA concentrate and tuna or palm oil, could increase the EPA and DHA incorporation. The R. miehei, rice bran, and CPL lipases unabled to incorporate DHA into DHA-containing glyceride molecule, whereas C. antartica lipase had the capability in high ratio of n-3 PUFA concentrate to oil. Therefore, the lipases were easier to incorporate n-3 PUFA into palm oil than tuna oil, since the TAG molecules of palm oil was not as complex as tuna oil. It could be suggested that the lipases did not only have acyl chain and positional specificity, but also the whole glyceride structure specificity.Keywords : acidolysis, lipase, n-3 PUFA, palm oil, specificity, tuna oil.